Lower-zone emphysema in young patients without α(1)-antitrypsin deficiency - Martelli, Nestor A. (1974)
Martelli, N. A., Goldman, E., and Roncoroni, A. J. (1974).Thorax, 29, 237-244. Lowerzone emphysema in young patients without α(1)-antitrypsin deficiency. Three young patients with radiographic pulmonary emphysema predominantly in the lower zones are reported. The clinical and physiological features were those observed in severe pulmonary emphysema. Predominance of the main lesions in the lower zones was confirmed in two cases by selective pulmonary angiography. One of the patients died and extensive panlobular emphysema was found at necropsy. Although the similarities between our patients and those with emphysema and α(1)-antitrypsin deficiency were remarkable, the latter condition was ruled out.